The Role of Energy Equity and Income Inequality in Environmental Sustainability - Pamela E. Ofori; Isaac K. Ofori; Kenneth Annan (Journal of Cleaner Production, 2024)
Progress in energy equity, income equality, and environmental quality are fundamental to sustainable development. However, studies providing evidence-based recommendations concerning the joint effect of energy equity and income inequality on environmental sustainability in Africa are lacking. This study fills this gap by using a panel dataset covering 41 African countries from 2008-2019. Results from the Driscoll-Kraay standard errors and the dynamic system GMM estimators reveal the following: (1) energy equity promotes environmental quality, whereas income inequality hampers it, and (2) income inequality nullifies the favourable environmental gains of energy equity. These findings remain consistent when we use the ecological footprint as an alternative measure of environmental quality. We conclude that addressing income inequality is essential for ensuring that energy equity enhances environmental quality. Policymakers should prioritise energy equity and fairer income distribution initiatives to achieve sustainable development goals.
Keywords: D31; O13; O55; Q40; Q5; Q53; 330; Africa; Energy equity; Environmental quality; Income inequality